An Analysis Conjunctions Used in Tripadvisor Reviews of Prama Sanur Beach Hotel - Pande Putu Dian Pramesti; Ida Ayu Putri Gita Ardiantari (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This study investigates the usage and functions of conjunctions in TripAdvisor reviews of the Prama Sanur Beach Hotel. Utilizing descriptive methods, both formal and informal language in the reviews were meticulously scrutinized. The data encompassed TripAdvisor reviews from January 2018 to December 2019. Conjunctions were discerned employing note-taking techniques and were subsequently classified. Out of 235 instances, 13 were deliberately chosen for in-depth analysis. The findings unveil four primary types of conjunctions: additive, adversative, causal, and temporal, with adversative conjunctions emerging as the most prevalent. Moreover, the study acknowledges potential limitations, such as inherent biases in the selection of reviews and constraints in the analytical approach. Additionally, it is noted that conjunctions predominantly manifest as individual words. Furthermore, the study discerns common patterns and recurring themes within these conjunction types.